Signal Processing A Mathematical Approach (2nd Edition) - Byrne, Charles L. (CRC Press, 2014)
This book explains how mathematical tools can be used to solve problems in signal processing. Assuming an advanced undergraduate- or graduate-level understanding of mathematics, this second edition contains new chapters on convolution and the vector DFT, plane-wave propagation, and the BLUE and Kalman filters. It expands the material on Fourier analysis to three new chapters to provide additional background information, presents real-world examples of applications that demonstrate how mathematics is used in remote sensing, and includes robust appendices and problems for classroom use.
Description based on print version record.
KU Select 2018: STEM Backlist Books
Keywords: Mathematics / Applied; Mathematics; Electronic books